The two faces of metal ions: From implants rejection to tissue repair/regeneration. (April 2016) - Vasconcelos, Daniel M.; Santos, Susana G.; Lamghari, Meriem; Barbosa, Mário A.
Abstract: The paradigm of metallic ions as exclusive toxic agents is changing. During the last 60 years, knowledge about toxicological and immunological reactions to metal particles and ions has advanced considerably. Hip prostheses, namely metal-on-metal bearings, have prompted studies about excessive and prolonged exposure to prosthetic debris. In that context, the interactions of metal particles and ions with cells and tissues are mostly harmful, inducing immune responses that lead to osteolysis and implant failure. However, in the last decade, new strategies to promote immunomodulation and healing have emerged based on the unique properties of metallic ions. The atom-size and charge enable ions to interact with key macromolecules (e.g. proteins, nucleic acids) that affect cellular function. Moreover, these agents are inexpensive, stable and can be integrated in biomaterials, which may open new avenues for a novel generation of medical devices. Herein, orthopedic devices are discussed as models for adverse responses to metal ions, and debated together with the potential to use metal ions-based therapies, thus bridging the gap between unmet clinical needs and cutting-edge research. In summary, this review addresses the two "faces" of metallic ions, from pathological responses to innovative research strategies that use metal ions for regenerative medicine.